A Case of Severe Generalized Granuloma Annulare Responding Well to Tofacitinib - Saman Al-Zahawi; Narges Ghandi; Vahidesadat Azhari; Kamran Balighi (Case Reports in Dermatological Medicine)
Granuloma annulare is a noninfectious, granulomatous skin disorder that typically presents as symmetrical, asymptomatic, annular, or arciform plaques with slightly raised edges, often found on the back of the hands or feet. This report highlights the successful use of tofacitinib in treating resistant/generalized granuloma annulare in a 66-year-old male with a known history of hepatitis B, demonstrating its potential as an effective therapeutic option.